The ERS approach to e-cigarettes is entirely rational. Issue 5 (7th May 2020) - Bush, Andrew; Bhatt, Jayesh Mahendra; Carroll, Will; Child, Frances; Connett, Gary; Doull, Iolo; Gilchrist, Francis; Grigg, Jonathan; Langton-Hewer, Simon; Legg, Julian; Lenney, Warren; Paton, James; et al.
The call for the European Respiratory Society (ERS) to change their e-cigarette and vaping policy, from honourable people with decades of experience fighting the evils of tobacco, is unfortunately misconceived. The three issues of greatest concern are acute toxicity, chronic toxicity and, most importantly, the effects on children and young people. The efficacy of e-cigarettes as an adjunct to smoking cessation are outwith the expertise of paediatric specialists, but we would ask for assurances that any benefits really do outweigh the risks to children and young people (below). Our comments on these key issues are as follows: The ERS has the right approach to e-cigarettes https://bit.ly/3ax72oe